A first attempt to prevent amblyopia and squint by spectacle correction of abnormal refractions from age 1 year. Issue 11 (November 1985) - Ingram, R M; Walker, C; Wilson, J M; Arnold, P E; Lucas, J; Dally, S
Abstract : Spectacle correction of unusually hypermetropic refractions from age 1 year did not reduce the incidence of squint or amblyopia, nor did it lead to a reduction in the severity of residual amblyopia after subsequent occlusion.